Minding the gap: Prioritization of care issues among nurse practitioners, family physicians and geriatricians when caring for the elderly. Issue 4 (July 2015) - Moore, Ainsley; Patterson, Christopher; Nair, Kalpana; Oliver, Doug; Brown, Allison; Keating, Patrick; Riva, John J.
Abstract Accumulating health problems of the elderly requires recognition of geriatric syndromes, while shifting away from a conventional disease-specific approach. We surveyed 179 practitioners representing Family Physicians (FPs), Nurse Practitioners (NPs) and geriatricians in Ontario, in order to quantify how they prioritize syndromes, diseases and conditions in the elderly. Identifying differences may inform opportunities for interprofessional sharing of expertise among professionals pursuing a common goal, which is expected to improve interprofessional collaboration. Our survey (response rate 36%) identifies that NP, FP and geriatrician respondents all recognize co-occurrence of "multiple morbidities" as one of the most frequently encountered issues when serving the elderly, however FPs and NPs place higher priority on managing individual chronic diseases than explicitly prioritizing geriatric syndromes. Our findings identify a need for a more clearly defined role for the geriatrician as syndrome-educator and implies further need for collaborative approaches to caring for seniors that values different professional's expertise.